The development of radio services in the Second Polish Republic. Social, strategic and political rationale - Kaszuba, Elżbieta (Radiofonizacja II Rzeczpospolitej. Przesłanki społeczne, strategiczne i polityczne, 2014)
In the Second Polish Republic, to about the mid-twenties, radio broadcasting was only a technical innovation. A fundamental change in this area was carried out by a private- state company Polish Radio, after a nation-wide state license for “broadcasting”, that is a radio for the masses, was granted to it, on August 18, 1925..Polish Radio launched the enduring native radio and began to realise a great project of development of radio services in the country. Stimulating the development of radio broadcasting, in addition to economic significance, gained social, strategic and political importance. Radio ensured the freedom of communication, therefore it could prove useful in supporting the process of unifying the newly recovered state and society and expanded the access of all social groups including an underprivileged social class because of poverty, illiteracy, living in remote areas and being removed from the centre in terms of advancement of civilization to the modern informative, educational and cultural medium.
Społeczeństwo i Ekonomia = Society and Economics, 2014, Nr 1 (1), s. 117-132
Keywords: radio services development; education; propaganda; integration; radiofonizacja; edukacja; integracja